Comprehensive Study of Ethical Dilemmas in General Healthcare Practices - Alsawar, Mohammed Saeed Mesfer; Alsawar, Alhassan Mohammed; Haydar, Ali Mahdi Saleh; Hammad, Hussain Mohammed; Hamoud, Sarah Abdullah; Moafa, Abdulrhman Ibrahim Abdu; Hakami, Ali Ahmed Ali; Moafa, Majed Ibrahim Abdu; Alaklabi, Khalid Ali Khalid; Issa, Halima Ahmed Allallah (Journal of Ecohumanism, 2024)
The focus of this paper is the healthcare sector, a caring industry that seeks to improve the health of individual patients but presents many ethical issues in different settings. This paper describes general practice ethical dilemmas arising from the healthcare setting regarding patient autonomy, privacy, palliation, informed consent, and rationing. Using case studies and literature and integrating both qualitative and quantitative analysis, the research questions aim to identify the causes of such ethical dilemmas and how to solve them. According to proof deduced from the study, HCS personnel report working in an environment that constantly presents ethical dilemmas; choices are made between/within professional responsibility, patients’ rights, and compliance with institutional policies. This study underlines the necessity to define ethical principles for decision-making in the most ambiguous cases and develop extensive training courses for the healthcare staff. Solutions are noted to involve improving communication between other healthcare departments, improving patients’ relationships with their care providers, and increasing healthcare policies’ legal and moral standards.